PL.05 Use of Quantitative Fetal Fibronection For Prediction of Spontaneous Preterm Birth in High Risk Asymptomatic Women. (26th April 2013) - Abbott, DS; Chandiramani, M; Seed, PT; Kemp, J; Tribe, RM; Shennan, AH
Abstract : Introduction: Prediction of spontaneous preterm birth (sPTB) remains a challenge in obstetrics. Fetal fibronectin (fFN) is a strong negative predictor of sPTB (Berghella et al, 2008). Quantitative measurements of fFN may provide additional discriminatory information, improve positive prediction and be more clinically useful in predicting risk and outcome. The aim of this study was to determine if risk of sPTB correlated with concentration of fFN. Study design: A prospective blinded study of cervico-vaginal fFN concentration (ng/mL) in asymptomatic women considered at high risk of spontaneous preterm birth (n = 744; 22–27 +6 weeks') using a 10Q analyser (Hologic ® ). Clinicians were blinded to the result until post-delivery but the qualitative TLIIQ (Hologic ® ) fFN result was made available. Results: The rate of sPTB (<34 weeks') was lowest (2%) for women with concentrations 0–9 ng/ml, and highest for those with concentrations ≥200 ng/mL (31%). Compared to <10 ng/mL fFN, the relative risk of delivery was: (10–49 ng/ml) 4.3 (95% CI 0.03 to 0.13), (50–199 ng/mL) 4.3 (95% CI 0.005 to 0.15), (≥200 ng/mL) 13 (95% CI 0.16 to 0.42). The positive predictive value for sPTB (<34 weeks') increased from 15, 19, 31% with increasing thresholds (10, 50, 200 ng/mL respectively), yet negative prediction remained >95%. Conclusion: Risk of sPTB is increased for concentrations above 10 ng/mL. Quantitative fFN provides additional thresholds (10 and 200 ng/mL) over the qualitative method (50 ng/mL) to discriminate risk of sPTB in high risk asymptomatic women.